S. Ciarán's church and his lands: a study of the history and development of Clonmacnoise - Kehnel, Annette (Trinity College (Dublin, Ireland). Department of History, 1995)
Clonmacnois was founded in the middle of the sixth century, as a place of contemplation by S. Ciarán. In the course of the following two centuries it became one of the largest churches in Ireland. A considerable number of lay people, monastic clients, lived nearby the church, employed in work on the ecclesiastical estate in the service of the abbot of Clonmacnois as their ecclesiastical overlord. Furthermore the abbots of Clonmacnois held lands in a number of associated churches, spread all over the country, which were under the ecclesiastical jurisdiction of its bishop. In the thesis the organisation of the church of Clonmacnois as an ecclesiastical institution will be discussed. It seems that government was in the hands of a lay ecclesiastical ruling class, who in a widely spread network of relationships exercised power over lands and people, as landlords of a large estate. The power held by those in government of the church relied very much on constant interaction with the secular rulers at the time. Close links with the leading dynasties in Connacht are apparent for the early period, from the seventh to the ninth century. From the late ninth century onwards the Clann Cholmáin kings of Mide assume increasing importance as the secular patrons of the ecclesiastical estate. With the decline of the kingdom of Mide in the course of the eleventh century, smaller kingdoms in the immediate neighbourhood of Clonmacnois, such as Tethba and Ui Maine, became closely involved in the fortunes of the nearby ecclesiastical estate, and families from these territories appear frequently in leading offices. Finally, with the close of the eleventh century, the Ua Conchobair kings of Connacht found a close ally in Clonmacnois, a friendship with was maintained throughout the twelfth down to the early thirteenth century.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin